Pembelajaran Fisika melalui Bencana Alam: Strategi Meningkatkan Kemampuan Berpikir Kritis Peserta Didik - Nuryanti, Refina; Hariyono, Eko (Pendidikan Fisika Universitas Nurul Huda, 2025)
This study aims to analyze the improvement of students' critical thinking skills after implementing physics learning integrated with natural disaster mitigation of volcanic eruptions. This type of research is quasi experimental and Non-equivalent Control Group pre-test and post-test Design conducted at one of the SMAN in Kediri Regency. The number of samples in this study were 66 students in two classes selected by purposive sampling. The research instrument was in the form of a critical thinking skills test which was analyzed using excel software to determine how much the students' critical thinking skills improved between the experimental class and the control class through the n-gain value. Based on the research that has been done, the results show that the average n-gain of the experimental class is higher at 0.60 compared to the control class of 0.48. These results indicate that the application of the PBL model integrated with volcanic eruption mitigation in experimental classes is more influential in improving students' critical thinking skills than control classes that use conventional learning